The city of ember : book 1 - DuPrau, Jeanne (U.S.A. : Scholastic INC, 2016)
The city of ember was built as a last refuge for the human race. Two hundred years laer, supplies are running low and terrifying blackouts are sweeping through the streets. It's only a matter of time before the lights go out and never come back on again
Keywords: ENGLISH LITERATURE; ADVENTURE STORIES